1978
DOI: 10.1111/j.1476-5381.1978.tb08657.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin, Protein Transacetylation and Inhibition of Prostaglandin Synthetase in the Kidney

Abstract: The effect of aspirin on the kidney has been investigated in mice and rabbits. [Acetyl‐14C]‐aspirin was administered intraperitoneally in doses ranging from subtherapeutic to toxic. The degree of acetylation of protein was determined by the radioactivity remaining on protein precipitates of renal cortex and medulla after sequential washing designed to remove non‐covalently bound material. Controls were established, by the use of [carboxyl‐14C]‐aspirin. The acetyl‐14C residue was bound to renal proteins in a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…It is well known that the acetyl group of aspirin can acetylate several proteins other than COX ( Alfonso et al , 2009b ; Marimuthu et al , 2011 ; Bateman et al , 2013 ). Experiments with radiolabelled 3 H or 14 C aspirin demonstrated that aspirin acetylates several proteins in vitro and in vivo through a transacetylation reaction ( Hawkins et al , 1968 ; Caterson et al , 1978 ; Rainsford et al , 1983 ). Aspirin acetylates human serum albumin and fibrinogen in vitro and in vivo ( Hawkins et al , 1968 ; Bjornsson et al , 1989 ).…”
Section: Extra-cox Acetylation Targetsmentioning
confidence: 99%
“…It is well known that the acetyl group of aspirin can acetylate several proteins other than COX ( Alfonso et al , 2009b ; Marimuthu et al , 2011 ; Bateman et al , 2013 ). Experiments with radiolabelled 3 H or 14 C aspirin demonstrated that aspirin acetylates several proteins in vitro and in vivo through a transacetylation reaction ( Hawkins et al , 1968 ; Caterson et al , 1978 ; Rainsford et al , 1983 ). Aspirin acetylates human serum albumin and fibrinogen in vitro and in vivo ( Hawkins et al , 1968 ; Bjornsson et al , 1989 ).…”
Section: Extra-cox Acetylation Targetsmentioning
confidence: 99%
“…Another study revealed that aspirin at micromolar concentrations acetylated rBC membrane peptides (30). elsewhere, aspirin was shown to acetylate renal cortical and medullary proteins after in vivo administration (15). This acetylation of proteins was rapid and increased the half-life of these proteins to more than 130 h. There is also a study that demonstrated the ability of aspirin to acetylate ubiquitin in vitro (31).…”
Section: Acetylation Of Other Proteins and Biomolecules By Aspirinmentioning
confidence: 87%
“…It is not at present clear how many of these lysine residues, besides K382, are acetylated by aspirin (35). In view of previous reports on the ability of aspirin to acetylate proteins through a transacetylation reaction (8,(12)(13)(14)(15), it is likely that aspirin targets multiple lysine residues on p53. Consistent with this notion, we observed that the incubation of purified recombinant p53 with low (100 µM) as well as high (2.5 mM) concentrations of aspirin resulted in p53 acetylation at lysine 382 (Fig.…”
Section: Acetylation Of P53 By Aspirinmentioning
confidence: 99%
See 1 more Smart Citation
“…While aspirin's ability to acetylate and inhibit COX enzyme activity is well known (8,9), limited information is available as to whether it can acetylate other proteins and alter their functions (15,16). We recently demonstrated in MDA-MB-231 human breast cancer cells that one of the acetylation targets of aspirin is the tumor suppressor protein, p53 (17).…”
Section: Introductionmentioning
confidence: 99%